2016
DOI: 10.1098/rspb.2016.1058
|View full text |Cite
|
Sign up to set email alerts
|

Learning to cope: vocal adjustment to urban noise is correlated with prior experience in black-capped chickadees

Abstract: Urban noise can interfere with avian communication through masking, but birds can reduce this interference by altering their vocalizations. Although several experimental studies indicate that birds can rapidly change their vocalizations in response to sudden increases in ambient noise, none have investigated whether this is a learned response that depends on previous exposure. Black-capped chickadees (Poecile atricapillus) change the frequency of their songs in response to both fluctuating traffic noise and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 58 publications
3
77
3
Order By: Relevance
“…Detrimental effects of noise, however, can be mitigated by behavioural and phenotypic plasticity of animals against noise (Lampe, Reinhold, & Schmoll, ; LaZerte, Slabbekoorn, & Otter, ). Indeed, there is plenty of evidence showing that signallers can reduce negative effects of acoustic masking by modifying their signal properties such as frequencies (Cunnington & Fahrig, ; Francis, Ortega, & Cruz, ; Patricelli & Blickley, ; Slabbekoorn & Peet, ) or amplitudes (i.e., the Lombard effects) (Halfwerk, Lea, Guerra, Page, & Ryan, ; Zollinger & Brumm, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detrimental effects of noise, however, can be mitigated by behavioural and phenotypic plasticity of animals against noise (Lampe, Reinhold, & Schmoll, ; LaZerte, Slabbekoorn, & Otter, ). Indeed, there is plenty of evidence showing that signallers can reduce negative effects of acoustic masking by modifying their signal properties such as frequencies (Cunnington & Fahrig, ; Francis, Ortega, & Cruz, ; Patricelli & Blickley, ; Slabbekoorn & Peet, ) or amplitudes (i.e., the Lombard effects) (Halfwerk, Lea, Guerra, Page, & Ryan, ; Zollinger & Brumm, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is plenty of evidence showing that signallers can reduce negative effects of acoustic masking by modifying their signal properties such as frequencies (Cunnington & Fahrig, ; Francis, Ortega, & Cruz, ; Patricelli & Blickley, ; Slabbekoorn & Peet, ) or amplitudes (i.e., the Lombard effects) (Halfwerk, Lea, Guerra, Page, & Ryan, ; Zollinger & Brumm, ). Moreover, recent studies have shown that prior experience with noise can be related to such modifiability in signallers (Gentry, Derryberry, Danner, Danner, & Luther, ; LaZerte et al., ). Although evidence of signaller responses to noise is quite common (Slabbekoorn, ), behavioural responses of signal receivers has received comparably very little attention (but see Kleist, Guralnick, Cruz, & Francis, ; Luther, Danner, Danner, Gentry, & Derryberry, ) and, to our knowledge, only one study has investigated behavioural plasticity in receivers in response to noise (Halfwerk, Bot, & Slabbekoorn, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we found evidence that black-capped chickadees from noisy areas seem to be better in using immediate plasticity to adjust signals to minimize masking than are males from quiet areas (LaZerte et al, 2016). Previously, we found evidence that black-capped chickadees from noisy areas seem to be better in using immediate plasticity to adjust signals to minimize masking than are males from quiet areas (LaZerte et al, 2016).…”
Section: Familiarity With Noisementioning
confidence: 86%
“…This highlights the importance again of considering context and the effect that long-term familiarity with anthropogenic noise may have on free-ranging animals (Gentry et al, 2017;Harding et al, 2018;LaZerte et al, 2016;Nedelec et al, 2016). Further laboratory and field studies of receiver detection and discrimination are needed to help determine whether this is the result of improved perception in noisy habitats by urban receivers or increased aggression in urban habitats, or some combination of the two.…”
Section: Con Clus Ionsmentioning
confidence: 99%